1985
DOI: 10.1002/ijc.2910350403
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous melanoma in relation to intermittent and constant sun exposure—the western canada melanoma study

Abstract: The histories of exposure to sun through occupational, recreational and vacation activities of 595 patients with newly incident cutaneous melanoma excluding lentigo maligna and acral lentiginous melanoma, were compared to those of comparison subjects drawn randomly from the same population and matched for age, sex and province of residence in Western Canada. Significant increases in risk were seen with increasing amount of sun exposure through outdoor activities associated with recreation and vacations; activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
154
0
5

Year Published

1989
1989
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(169 citation statements)
references
References 16 publications
10
154
0
5
Order By: Relevance
“…A maior parte das capitais brasileiras encontra-se perto do litoral, e as diversas situações de exposição (lazer, trabalho, atividade doméstica) podem ter influências importantes nos níveis de exposição solar cumulativos 11 . Conseqüente-mente, ao juntarmos diversas capitais por região, podemos estar juntando cidades com características diferentes de situação de exposição solar (por exemplo, capitais localizadas perto do litoral e no interior).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A maior parte das capitais brasileiras encontra-se perto do litoral, e as diversas situações de exposição (lazer, trabalho, atividade doméstica) podem ter influências importantes nos níveis de exposição solar cumulativos 11 . Conseqüente-mente, ao juntarmos diversas capitais por região, podemos estar juntando cidades com características diferentes de situação de exposição solar (por exemplo, capitais localizadas perto do litoral e no interior).…”
Section: Discussionunclassified
“…Associadas a esses hábitos de vida e proteção, distinguem-se três situações de exposição solar: no lazer, no trabalho e na realização de atividades domésticas 10,11 .…”
Section: Introductionunclassified
“…Epidemiological studies have revealed a correlation between exposure to sunlight and the development of cutaneous melanoma, especially of the lentigo maligna type but also of the more common types studied here (5)(6)(7)(8)19). This finding suggests that UV irradiation damages the DNA of melanocytes that might contribute to the development of neoplasia.…”
mentioning
confidence: 94%
“…We therefore investigated the precise sites of the tumors on the bodies of melanoma patients with respect to sun exposure. Exposure was categorized as continuous, intermittent, or rare (5)(6)(7)(8)18; see footnote c, Table 1). For 31 of the patients, localization of the primary tumor was indicated in the clinical record: in 10 patients on continuously exposed sites, in 16 on intermittently exposed sites, and in 5 on rarely exposed sites (Table 1).…”
mentioning
confidence: 99%
“…We selected melanocytic tumors for our study because of the close connection between melanoma etiology and ultraviolet exposure (15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%